Penetration of Triphenylphosphonium Derivatives through the Cell Envelope of Bacteria of Mycobacteriales Order - Pavel A. Nazarov; Konstantin B. Majorov; Alexander S. Apt; Maxim V. Skulachev (MDPI AG, 2023)
The penetration of substances through the bacterial cell envelope is a complex and underinvestigated process. Mitochondria-targeted antioxidant and antibiotic SkQ1 (10-(plastoquinonyl)decyltriphenylphosphonium) is an excellent model for studying the penetration of substances through the bacterial cell envelope. SkQ1 resistance in Gram-negative bacteria has been found to be dependent on the presence of the AcrAB-TolC pump, while Gram-positive bacteria do not have this pump but, instead, have a mycolic acid-containing cell wall that is a tough barrier against many antibiotics. Here, we report the bactericidal action of SkQ1 and dodecyl triphenylphospho-nium (C12TPP) against Rhodococcus fascians and Mycobacterium tuberculosis, pathogens of plants and humans. The mechanism of the bactericidal action is based on the penetration of SkQ1 and C12TPP through the cell envelope and the disruption of the bioenergetics of bacteria. One, but probably not the only such mechanism is a decrease in membrane potential, which is important for the implementation of many cellular processes. Thus, neither the presence of MDR pumps, nor the presence of porins, prevents the penetration of SkQ1 and C12TPP through the complex cell envelope of R. fascians and M. tuberculosis.